Prototype Sistem Inventory Control Berbasis Barcode Pada PT.Anugrah Distributor Indonesia - Jawahir Jawahir; Muhamad Ifran Sanni; Ahmad Kurniawan (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2020)
The rapid technological growth should be able to support industrial activities, this occurs in checking the inventory of goods at PT.Anugrah Distributor Indonesia, at this time the warehouse admin must check and then input data on so many stock items that are often missed so it takes a long time in checking stock of goods. By scanning items by using a barcode, displaying the history of the incoming and outgoing goods code to the warehouse and being able to manage the results of scanning based on the time and date in real-time. The use of SWOT or Strengths, Weaknesses, Opportunities & Threats methods as well as to obtain information that is appropriate to the problem that researchers must overcome using interviews, observation and literature studies. and to design a system design using UML and then using PHP (Hypertext) and Sublime Text applications. The inventory control system application will be able to facilitate the recording and search of inventory data in real-time as well as controlling the stock of goods in the company